Do acoustically detectable species reflect overall diversity? A case study from Australia's arid zone. Issue 3 (19th July 2020) - Smith, David G.; Truskinger, Anthony; Roe, Paul; Watson, David M.
Abstract: In recent years, passive acoustic monitoring has emerged as a reliable method for monitoring soniferous fauna, with numerous studies finding estimates of species richness and community composition are comparable with estimates derived from conventional field surveys. Most of these studies compare point counts of forest bird communities with contemporaneous short‐duration acoustic recordings, but several questions remain. How do these two methods compare in more open, arid ecosystems, how does applying methods optimally influence comparisons, and how do patterns in acoustically detectable species compare with overall patterns? Here we demonstrate techniques for improving sampling of acoustic data and conduct acoustic surveys to estimate species richness from ephemeral creek‐lines in the Australian arid zone using a long‐term passively derived acoustic dataset. We examine these results in the context of long‐term observer‐based transect surveys conducted along the same creek‐lines to define species within the avian assemblage that are acoustically detectable or acoustically undetectable/cryptic. Our data suggest that some species were consistently missed by acoustic surveys, but most belonged to groups that are typically excluded from inventories prior to analysis including rare species, raptors, waterbirds, swallows and nocturnal birds. Further, the relative diversities of sites were well estimated by acoustic surveys, with variations between sites reflecting those estimated by observer‐based field surveys. This suggests that in our study system, acoustically detectable species are reliable indicators of overall species richness. Field‐based surveys will remain an important component of sampling in arid ecosystems and we highlight the value of applying acoustic and conventional field‐based surveys in a complementary manner. This approach allows large, publishable datasets to be generated by exploiting the temporal reach of acoustic sensors, while also maximizing detections of acoustically cryptic species via field‐based surveys. We argue that acoustic monitoring has the potential to facilitate greater research effort in largely research‐deficient arid ecosystems. Abstract : We conducted bird surveys on creek‐lines in the Australian desert using conventional transect surveys and acoustic monitoring. We found that both methods achieved similar species richness estimates and revealed comparable patterns of richness between creek‐lines. We outline novel methods for improving the efficiency of aural acoustic bird surveys and suggest that acoustic monitoring can play an important role in monitoring bird assemblages in remote areas.